Transmission line with gaseous cavitation - Abdul Muhaimin Abdul Malik (2015)
Gaseous cavitation which is also termed gas release was studied comprehensively to improve a vaporous cavitation model in transmission lines. Comparisons were made between a two-phase homogeneous equilibrium gaseous cavitation model to a two-phase homogeneous equilibrium vaporous cavitation model in this paper. The latter exclude the gaseous cavitation phenomena in its modelling which resulted in inaccuracies in their predictions. Firstly, the governing equations with the implementation of the gas term are developed and the method of characteristics was utilized to simplify the governing equations into four ordinary differential equations. They are then integrated to get finite difference equations to be solved using a computer software. The model is able to predict results that are more similar to the experimental results with the inclusion of the gas cavitation phenomena.